2021
DOI: 10.1556/606.2020.00127
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and numerical simulation of residual stress in multi-pass pipe welds

Abstract: A numerical simulation procedure is presented to predict residual stress states in multi-pass welds in oil transportation pipes. In this paper, a two-dimensional thermo-mechanical finite element model is used to calculate the temperature distribution, hardness, and the distribution of residual stresses during multi-pass welding of pipes of dissimilar metals and varying thicknesses. In this model, the temperature dependence of the thermal and mechanical properties of the material was considered. The present mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…It calculated the residual stress distribution, temperature and hardness distribution of multi pass welding through two-dimensional thermal finite element model, and takes temperature dependence as an important factor to consider. The results showed that the simulation results have a high degree of consistency with the test results, which can save time [15]. P.Asadi's team raised a non coupled thermal 3D model for numerical analysis of residual stress.…”
Section: Related Workmentioning
confidence: 84%
“…It calculated the residual stress distribution, temperature and hardness distribution of multi pass welding through two-dimensional thermal finite element model, and takes temperature dependence as an important factor to consider. The results showed that the simulation results have a high degree of consistency with the test results, which can save time [15]. P.Asadi's team raised a non coupled thermal 3D model for numerical analysis of residual stress.…”
Section: Related Workmentioning
confidence: 84%
“…The most recent study by [5] has used simple BERT architecture without considering the importance of preprocessing steps like handling of Not a Number (NaN) values, stopword removal, PoS tagging, contractions, stemming and lemmatization, which suggests that probably their model was not trained on good data, which may have led to model over-fitting [21][22][23][24]. The researchers also did not consider the fine-tuning strategies [25][26], which supplement the model to achieve better results. In this study, all the steps mentioned above were performed and try to identify the abuse in the multilingual text as it is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%